2023
DOI: 10.1111/obr.13626
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants associated with weight loss and metabolic outcomes after bariatric surgery: A systematic review

Rieneke van der Meer,
Siham A. Mohamed,
Valerie M. Monpellier
et al.

Abstract: SummaryThe extent to which genetic variations contribute to interindividual differences in weight loss and metabolic outcomes after bariatric surgery is unknown. Identifying genetic variants that impact surgery outcomes may contribute to clinical decision making. This review evaluates current evidence addressing the association of genetic variants with weight loss and changes in metabolic parameters after bariatric surgery. A search was conducted using Medline, Embase, Scopus, Web of Science, and Cochrane Libr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 112 publications
0
2
0
Order By: Relevance
“…Genome-wide association studies have found many SNP loci that are significantly correlated with variation in response to dietary interventions for weight loss [ 16 ]. Genetic variations may also contribute to inter-individual differences in weight loss and metabolic outcomes as well as weight regain after bariatric surgery [ 17 , 18 , 20 ]. In a small study, researchers found a correlation between weight regain and specific genetic variations among patients.…”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide association studies have found many SNP loci that are significantly correlated with variation in response to dietary interventions for weight loss [ 16 ]. Genetic variations may also contribute to inter-individual differences in weight loss and metabolic outcomes as well as weight regain after bariatric surgery [ 17 , 18 , 20 ]. In a small study, researchers found a correlation between weight regain and specific genetic variations among patients.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent review, van der Meer et al [ 230 ] suggest that there is limited evidence supporting a role for genetic variants in outcomes following bariatric surgery. They suggest that more evidence and studies are needed to replicate findings across sexes and ethnicities.…”
Section: Weight Regain Following Bariatric Surgerymentioning
confidence: 99%